The TREX project - Kroča, Petr; Čáp, Jiří; Šohajek, Petr (Kaunas University of Technology, 2019)
The article presents the results of the international research and development project EUREKA No. LF 14003 called TREX, which was dealt with by OLTIS Group in 2014-2017. It includes the definition of the issue and its presentation, followed by a technical and technological approach to the preparation, negotiation and implementation of transport of extraordinary consignments in the proposed information system. Individual modules and functionalities of the information system, including their use, are analysed.
TREX projekt
Keywords: extraordinary consignment transport; TREX; EUREKA; information system; freight rail transport; transport path; mimořádné zásilky; TREX; EUREKA; informační systém; nákladní železniční doprava; přepravní trasa